General Common Fixed Point Theorems for Compatible Mappings of Type (C) - Bouhadjera, Hakima (Sarajevo Journal of Mathematics, 2024)
In this note, we prove a common fixed point theorem for four compatible mappings of type (C) satisfying an implicit relation. This theorem generalizes, improves and extends the result of Popa [6] and others. 2000 Mathematics Subject Classification. 47H10, 54H25